Analisis Pengaruh Intervensi Mertua dalam Penyelesaian Konflik Rumah Tangga Anak terhadap Keharmonisan Keluarga di Desa Masbagik Perspektif Hukum Keluarga Islam - Nuur Jauzaa' Maulida Husna; Muhsan Syarafuddin (Family Law Study Program, Faculty of Sharia and Law, UIN Sunan Gunung Djati Bandung, 2025)
This study aims to analyze the influence of in-laws' intervention in resolving marital conflicts of their children on household harmony in Masbagik Selatan Village. This is based on real-life occurrences within the community of Masbagik Selatan, East Lombok, where several cases involve in-laws intervening or becoming involved in their children's domestic conflicts. This research is a case study employing a qualitative approach to explore the phenomena occurring in the field. The data used in this study consist of primary data obtained through observations and interviews with the people of Masbagik Selatan, as well as secondary data gathered through literature relevant to the research focus. The findings reveal that in-laws’ intervention in resolving their children’s marital conflicts takes various forms. Interventions in the form of providing advice can have a positive impact on household harmony, whereas interventions involving direct control over the conflict tend to have a negative impact on the resolution of the children’s marital disputes